The family in patriotic education of young learners living in the United Kingdom as an example of foreign country (in 1945–1989) - Zamecka-Zalas, Olga (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2016)
The article deals with the role of the family in thepatriotic education of young learners living in a foreign country. The essential role of the family was to develop the national identity, to make the children feel proud of their country and to prevent them having a sense of social inferiority. Patriotic education was to instil love to an unknown country – Poland and a national identity in young learners, but mainly to give new perspectives on spiritual life. Some forms and methods in patriotic education were described in this article, e.g. teaching children about national traditions, monuments and church or state celebrations, reminding about the necessity of cultivating holiday customs and traditions and about the central role of the mother in the family. Apart from that Polish folklore played a vital role in educating children abroad, e.g. folk music, dance, songs and handicrafts or national costumes. The children had to learn to love their country as well as to live in a Polish family with all it customs, traditions and language to feel as Polish citizens still living in a foreign country. The article puts stress on the significance of cooperation between parents and Polish schools in educating children in Britain. The main aim of the close cooperation was to develop children and their personalities. Some forms and ways of interactions analysed in this paper were based on such articles in: „Wiadomości Nauczycielskie”, „Dziennik Polski” or „Dziennik Żołnierza”.
Keywords: family; patriotic education; child/young learne